Effect of halogen addition to monolayer protected gold nanoparticles - Singh, Sanjay; Pasricha, Renu; Bhatta, Umananda M.; Satyam, P. V.; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2007)
The effects of N-halosuccinimide and halogen addition to monolayer protected gold nanoparticles (Au NPs) dispersed in organic media are described. Contrary to the expectation that nanoparticles dispersed in organic media are stable against aggregation, N-iodosuccinimide addition induced aggregation of octadecylamine capped gold nanoparticles in chloroform or toluene. It was observed that even KI and CuI addition could bring about the aggregation though they are very sparingly soluble in organic solvents. It was also found that even molecular iodine could bring about the above mentioned aggregation. Interestingly, when CuI is used the aggregated structures readily convert to very thin flat nanostructures upon exposure to an electron beam or UV irradiation. In fact when the aggregation is induced by the addition of KI or N-iodosuccinamide we do not see the flattening of the aggregated structures exemplifying the important role of Cu ions in making these flat structures.